Effect of Variable Implant Tip Distances on Stress Distribution around the Mental Foramen: A Finite Element Analysis - Al Qahtani, Waleed M. S. (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aimed to evaluate the effect of gap between traditional implant tip and mental nerve using finite element analysis. METHODS: Four finite element models (FEM) were prepared for dummy crowns that were supported by traditional implants that were placed vertically in laser scanned mandibular bone geometry. Where gap distance were designed to be 1.5, 2.0, 2.5, and 3.0 mm. Dummy crown, 50 μm cement layer, and implant complex models’ components were modeled in 3D on engineering computer-aided design (CAD)/CAD (computer-aided manufacturer) software formerly collected in Finite Element Analysis package. Each model was subjected to two loading cases as 150N compressive load at central fossa, and 50N Oblique (45º) load at central fossa of the dummy crown. RESULTS: Good agreement of the FEM was obtained when compared to similar studies. Under applied study loads, all resulting values of stresses and deformations of the four models were within physiological limits. The obtained data showed no effect on cortical bone, implant complex, cement layer, and dummy crown to changing of gap distance. In addition, the cancellous bone, especially around the mental canal, was considerably affected by the variation in that gap distance. CONCLUSION: Increasing the gap distance between the dental implant tips may reduce the stress and deformation around the mental canal. Minimum gap distance of order 2.5 mm is recommended to reduce stresses and deformations around canal to favorable limits, while more gap distance is also recommended with larger bone geometries.